Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2022
DOI: 10.1186/s12940-022-00929-w
|View full text |Cite|
|
Sign up to set email alerts
|

Bone mass density following developmental exposures to perfluoroalkyl substances (PFAS): a longitudinal cohort study

Abstract: Background Environmental exposures to industrial chemicals, including perfluoroalkyl substances (PFAS), may play a role in bone development and future risk of osteoporosis. However, as prospective evidence is limited, the role of developmental PFAS exposures in bone density changes in childhood is unclear. The objective of this study was to estimate associations between serum-PFAS concentrations measured in infancy and early childhood and areal bone mineral density (aBMD) measured at age 9 year… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 58 publications
0
3
0
Order By: Relevance
“…5,11,12 In the serum of fishery workers, PFAS levels ranged between 0.01 and 10,400 ng/mL, while those exposed to contaminated drinking water presented with levels ranging between 0.5 and 35.5 ng/mL, suggesting that occupational exposure can result in PFAS burdens 1−4 orders of magnitude higher than the general population. 13,14 PFAS has been detected in serum from the maternal chord and in newborn blood, demonstrating that these chemicals are capable of passing through the placental barrier. Estimates of the efficiency of placental transfer range between 30% and 79%.…”
Section: ■ Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…5,11,12 In the serum of fishery workers, PFAS levels ranged between 0.01 and 10,400 ng/mL, while those exposed to contaminated drinking water presented with levels ranging between 0.5 and 35.5 ng/mL, suggesting that occupational exposure can result in PFAS burdens 1−4 orders of magnitude higher than the general population. 13,14 PFAS has been detected in serum from the maternal chord and in newborn blood, demonstrating that these chemicals are capable of passing through the placental barrier. Estimates of the efficiency of placental transfer range between 30% and 79%.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Elsewhere, 21 PFAS compounds found upon post-mortem analysis revealed that in the kidney and lung, perfluorobutanoic acid was the most frequently found PFAS (and at highest concentrations with median values residing at 263 and 807 ng/g in the kidney and lung, respectively). ,, In the liver and brain, perfluorohexanoic acid showed the maximum levels (median: 68.3 and 141 ng/g, respectively), while perfluorooctanoic acid (PFOA) was the most prevalent PFAS in bone (median: 20.9 ng/g). ,, In the serum of fishery workers, PFAS levels ranged between 0.01 and 10,400 ng/mL, while those exposed to contaminated drinking water presented with levels ranging between 0.5 and 35.5 ng/mL, suggesting that occupational exposure can result in PFAS burdens 1–4 orders of magnitude higher than the general population. , PFAS has been detected in serum from the maternal chord and in newborn blood, demonstrating that these chemicals are capable of passing through the placental barrier. Estimates of the efficiency of placental transfer range between 30% and 79%. , Breast milk has been shown to account for 83–99% of PFAS total daily intake for infants. , Nevertheless, the initial underestimation of their environmental impact together with their widespread use has caused in the last decades an increased level of environmental contamination from poly- and perfluorinated compounds and, in particular, from PFAS. , Although, several efforts have been made for PFAS detection and removal from water and soil, addressing the consequences of their historical use remains a critical challenge.…”
Section: Introductionmentioning
confidence: 99%
“…Following publication of the original article [ 1 ], the affiliation details for Philippe Grandjean were incorrectly given as '2,7' but should have been '1,7'.…”
mentioning
confidence: 99%